(untitled) (American Journal of Islam and Society, 2000)
This article seeks to advance an Islamic perspective on Organization Development. Arguing that OD interventions not only seek to institute planned change within organizations, but also change individuals, cultures and societies, the authors suggest that OD interventions can become useful tools for bringing about comprehensive development in society. The authors advance an Islamic perspective on OD in the hope of transforming Muslim organizations and precipitate comprehensive development of Muslim societies.